Observation of isolated high-E-T photons in deep inelastic scattering - Chekanov, S; Derrick, M; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Antonioli, P; Bari, G; et al. (2004)
First measurements of cross sections for isolated prompt photon production in deep inelastic ep scattering have been made using the ZEUS detector at the HERA electron-proton collider using an integrated luminosity of 121 pb -1. A signal for isolated photons in the transverse energy and rapidity ranges 5<etγ<10gev -0.7<ηγ<0.9="" and="" exchanged="" for="" observed="" of="" photon="" q2="" the="" virtualities="" was="">35GeV2. Cross sections are presented for inclusive prompt photons and for those accompanied by a single jet in the range ETjet≥6GeV and -1. 5≤ηjet<1.8. Calculations at order α 3αs describe the data reasonably well. © 2004 Elsevier B.V. All rights reserved.</etγ<10gev>